Hospital selection framework for remote MCD patients based on fuzzy q-rung orthopair environment - Alamoodi, Abdullah Hussein (Tanjung Malim, 2023)
Hospital selection framework for remote MCD patients based on fuzzy q-rung orthopair environment by Alamoodi, Abdullah Hussein